2013
DOI: 10.1080/10942912.2011.587622
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and radical scavenging activities of Asphodelus aestivus Brot. extracts

Abstract: Asphodelus aestivusBrot. is a common spring-flowering geophyte encountered on the Marmara, Aegean, and Mediterrenean coasts of Turkey, which has been utilized traditionally for culinary and medicinal purposes. In the present study, different antioxidant tests were employed in order to evaluate the antioxidant activities of methanolic and acetone extracts of A. aestivus Brot. leaves. In addition, the results were compared with natural and synthetic antioxidants. The levels of total flavonoid, total chlorophyll,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
9
1
1
Order By: Relevance
“…In a study on the radical mopping effects of Asphodelus aestivus Brot. extracts conducted by Peksel and her colleagues, 1 mg/mL of methanolic extract exhibited a strong scavenging effect on superoxide radicals (47). These findings were found to be lower than the outcomes of the current study.…”
Section: Discussioncontrasting
confidence: 91%
“…In a study on the radical mopping effects of Asphodelus aestivus Brot. extracts conducted by Peksel and her colleagues, 1 mg/mL of methanolic extract exhibited a strong scavenging effect on superoxide radicals (47). These findings were found to be lower than the outcomes of the current study.…”
Section: Discussioncontrasting
confidence: 91%
“…Both leaf and root extracts showed strong antioxidant activity [15,68]. The root extract also showed significant anti-inflammatory properties, specifically anti-ulcer activity which is one of the documented uses in Turkish traditional medicine [32].…”
Section: Resultsmentioning
confidence: 99%
“…Root tubers are used as daily food, after being moistened and fried beforehand to eliminate the astringent compounds, and also the young stem, the leaves and the roasted seeds [2,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Daniels et al [33] found an increase in non-enzymatic antioxidant capacity based on total polyphenol content in bulbs and roots of South African bulbous geophyte Gethyllis multifolia L. Bolus under drought stress. Additionally, Peksel et al [34] showed that Asphodelus aestivus has powerful antioxidant activity that is based on non-enzymatic antioxidants. In our study, the high APX, CAT and SOD activities in the root tubers of A. aestivus can be related to this plant's life cycle, which consists of an active phase (autumn-late spring) and an inactive (summer) phase [19,24].…”
Section: Discussionmentioning
confidence: 99%